2001
DOI: 10.1046/j.1471-4159.2001.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

A significant increase in both basal and maximal calcineurin activity in the rat pilocarpine model of status epilepticus

Abstract: This study focused on the effects of status epilepticus on the activity of calcineurin, a neuronally enriched, calcium-dependent phosphatase. Calcineurin is an important modulator of many neuronal processes, including learning and memory, induction of apoptosis, receptor function and neuronal excitability. Therefore, a status epilepticus-induced alteration of the activity of this important phosphatase would have signi®cant physiological implications. Status epilepticus was induced by pilocarpine injection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 61 publications
8
68
0
1
Order By: Relevance
“…As shown in Figure 3B, CaN-A␣ expression was unchanged at 1 h after hypoxia compared with control levels (n ϭ 5 animals per group). These data indicate that the acute increase in CaN activity measured 1 h after hypoxia-induced seizures is not likely a result of a rapid increase in CaN expression but rather from an increase CaN activation state or kinetics, similar to that reported in adult status epilepticus models (Kurz et al, 2001). At 6 h after hypoxia, we observed a modest but nonsignificant increase (10%) in CaN-A␣ expression (n ϭ 5 per group) (data not shown).…”
Section: Can Activity Is Elevated In Hippocampal Slices After Hypoxiasupporting
confidence: 85%
See 3 more Smart Citations
“…As shown in Figure 3B, CaN-A␣ expression was unchanged at 1 h after hypoxia compared with control levels (n ϭ 5 animals per group). These data indicate that the acute increase in CaN activity measured 1 h after hypoxia-induced seizures is not likely a result of a rapid increase in CaN expression but rather from an increase CaN activation state or kinetics, similar to that reported in adult status epilepticus models (Kurz et al, 2001). At 6 h after hypoxia, we observed a modest but nonsignificant increase (10%) in CaN-A␣ expression (n ϭ 5 per group) (data not shown).…”
Section: Can Activity Is Elevated In Hippocampal Slices After Hypoxiasupporting
confidence: 85%
“…These data suggested that CaN kinetics were altered by hypoxia. Notably, an early increase in basal and maximal CaN activity also has been reported in the adult brain after experimental status epilepticus (Kurz et al, 2001). Ca 2ϩ influx through GluRs regulates Ca 2ϩ -dependent intracellular enzymes such as CaN (Snyder et al, 1998b;Morioka et al, 1999;Vignes, 2001;Shibasaki et al, 2002) and calcium/calmodulindependent protein kinase II (CaMKII) , and CaN can be activated by increased intracellular Ca 2ϩ specifically through AMPAR activation (Nishi et al, 2002).…”
Section: Calcineurin Activation After Hypoxia-induced Seizuresmentioning
confidence: 89%
See 2 more Smart Citations
“…High levels of Cn activity predispose thymocytes, T cells, Jurkat cells, and neuronal cells to apoptosis induced by T cell receptor activation, calcium ionophores, growth-factor deprivation, L-glutamate, and status epilepticus (18)(19)(20)(21). In our screen to identify new calpain substrates by using an in vitro small pool assay, we have identified mouse cain͞cabin1 as a putative calpain substrate.…”
mentioning
confidence: 99%